Virtual Tour: Supporting Tourism Promotion in Benteng Alla’ South Sulawesi - As’ad, Ihwana; Dewantara, Andi Harpeni; Najirah; Usman, Musrayani; Base, Nurul Hidayah (Research and Social Study Institute, 2022)
Benteng Alla is one of the historical sites that needs to be developed as an international tourist destination. It is located in Benteng Alla Utara Village, Baroko District, Enrekang Regency, South Sulawesi. This historical heritage has a beautiful panorama, historical value, and strategic location to visit as a tourist destination. Virtual tourism as an online interactive system is one of promotion strategies that could attract tourists to visit or even provide them some information needed before visiting Benteng Alla. The collection data in this community service employed observation, interviews, and documentation techniques. The document process was carried out by taking picture and videos that highlight the main sites and access to the location of Benteng Alla. These documentation footages then edited and packaged into a virtual tour video which could be widely accessed through YouTube platform. This online tour video is a digital media supporting virtual tours to promote Benteng Alla tourist destination nationally and internationally.